Review of An advanced guide to multilingualism by Larissa Aronin - Gabryś-Barker, Danuta (Studies in Second Language Learning and Teaching, 2023)
As a researcher in multilingualism and multilinguality, I always await any new publications by Larissa Aronin. They not only add to our understanding and knowledge of this fascinating field, but also inspire us to look into the various dimensions not yet explored by other researchers. A truly imaginative and inspiring mind, hers has been a significant contribution to models of multiple language acquisition, the theory of affordances (Singleton & Aronin, 2007), and the material culture of multilingualism, not to forget – what I consider to be her biggest and most fascinating area of research – dominant language constellations (Aronin & Vetter, 2021; Lo Bianco & Aronin, 2020,) and also, fairly recently and still at the developmental stage, the philosophy of multilingualism (Aronin & Politis, 2015).